2011
DOI: 10.1108/00021461111152573
|View full text |Cite
|
Sign up to set email alerts
|

Regulation and the financial performance of Canadian agribusinesses

Abstract: Purpose -The purpose of this paper is to investigate the relationships between regulatory changes, returns on equity and stock market valuations for Canadian food and non-food agribusinesses. Design/methodology/approach -Two empirical approaches are employed. First, an event study is used to evaluate the impact of official regulatory announcements on the stock market valuations of selected Canadian agribusinesses. Next, an approach introduced by Mishra et al. using the Du Pont expansion is applied to investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…This wealth effect of government policy suggests the impact of a support program on farm income volatility is indeterminate. Schaufele and Sparling (2011) looked at the effect of government regulation announcements rather than funding levels and found that the regulatory changes did not correspond to abnormal stock market valuations for Canadian agribusinesses.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…This wealth effect of government policy suggests the impact of a support program on farm income volatility is indeterminate. Schaufele and Sparling (2011) looked at the effect of government regulation announcements rather than funding levels and found that the regulatory changes did not correspond to abnormal stock market valuations for Canadian agribusinesses.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…an event). These price changes manifest through abnormal stock returns as a reflection of inherent changes in private revenue and cost changes by the affected firms (Pozo and Schroeder, 2016; Pruitt and Peterson, 1986; Salin and Hooker, 2001; Schaufele and Sparling, 2011) to the extent that the particular event is unanticipated by investors (Brown and Warner, 1980).…”
Section: Introductionmentioning
confidence: 99%
“…The potential difficulty associated with date choice is evidenced by a study of the Canadian stock market in which it was found that official regulatory announcements in the agribusiness sector in Canada do not move stock prices. Similar effects associated with official dates and announcements may exist in the US agribusiness sector (Schaufele and Sparling, 2011). For the long-window analysis the CAPM model was applied in a similar fashion using monthly return data, rather than daily return data, and the model was estimated using 36 months of monthly data ending 4 months before the first event.…”
Section: Methodsmentioning
confidence: 99%